2014
DOI: 10.1371/journal.pone.0086919
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic-Based Efavirenz Dose Modification: Suggestions for an African Population and the Different CYP2B6 Genotypes

Abstract: BackgroundPharmacogenetics contributes to inter-individual variability in pharmacokinetics (PK) of efavirenz (EFV), leading to variations in both efficacy and toxicity. The purpose of this study was to assess the effect of genetic factors on EFV pharmacokinetics, treatment outcomes and genotype based EFV dose recommendations for adult HIV-1 infected Ugandans.MethodsIn total, 556 steady-state plasma EFV concentrations from 99 HIV infected patients (64 female) treated with EFV/lamivudine/zidovidine were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 24 publications
6
60
0
Order By: Relevance
“…Besides, Rotger et al identified intracellular EFV concentration as a predictor of neuropsychological toxicity induced by EFV (21). Efforts to predict safety and efficacy of EFV have focused on characterizing the systemic pharmacokinetics (12,22,23). Borand et al (24) found no association between treatment failure and the recommended efavirenz concentrations in plasma below 1 mg/liter (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Rotger et al identified intracellular EFV concentration as a predictor of neuropsychological toxicity induced by EFV (21). Efforts to predict safety and efficacy of EFV have focused on characterizing the systemic pharmacokinetics (12,22,23). Borand et al (24) found no association between treatment failure and the recommended efavirenz concentrations in plasma below 1 mg/liter (6).…”
Section: Discussionmentioning
confidence: 99%
“…Compartmental models for EFV and 8OHEFV were parameterized as volumes (V c EFV, V p EFV, V c 8OHEFV, and V p 8OHEFV) and transfer rate constants (k 20 , k 23 , k 32 , k 45 , and k 54 ), with derived clearances (CL c EFV and CL p EFV are first-order clearance terms for EFV, while CL c 8OHEFV and CL p 8OHEFV represent clearances for 8OHEFV from the central to peripheral compartments, respectively). Since the absolute oral bioavailability (F) of EFV cannot be determined in the absence of intravenous administration, the fraction of metabolic conversion of EFV to 8OHEFV also cannot accurately be determined, and clearance and volume of distribution terms for both EFV and 8OHEFV represent apparent values, such as CL/F and V/F.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] This enzyme is highly susceptible to polymorphism and these polymorphs play a role in the variability of efavirenz plasma concentrations. [9] Functionally deficient alleles may result in higher plasma levels of efavirenz in patients receiving a standard dose of 600 mg daily because of decreased metabolism of efavirenz.…”
Section: Genetic Polymorphismsmentioning
confidence: 99%
“…8,9 The plasma levels of efavirenz as well as genetic polymorphisms in certain populations are thought to be the cause of these neuropsychiatric side effects. 3,10,11 There have been several studies 7,12,13,14,15 comparing efavirenz with various other treatments such as nevirapine, protease inhibitors, etravirine and raltegravir. In all instances, efavirenz was seen to induce neuropsychiatric side effects more frequently than these other treatments.…”
Section: Introductionmentioning
confidence: 99%